Mapping deserted settlements in the Peloponnese, eighteenth–twentieth centuries: desertion patterns at the end of the Greek Revolution. Issue 2 (3rd July 2022) - Festas, Michael; Athanasouli, Anna; Dimitropoulos, Dimitris
Abstract : Focusing on the case of the Peloponnese, in southwestern Greece, at the end of the Greek Revolution (1821–1830), this article examines the question of deserted settlements in Greece within its historiographical, conceptual, methodological, and spatial framework. The juxtaposition of population enumerations with other text sources, historical and digital maps, and toponymic research has provided evidence for the permanent desertion of 57 settlements at the end of the revolution, which represent approximately a quarter of the total number of settlements that were abandoned in the Peloponnese during the nineteenth and twentieth centuries. Most of these settlements were small in size and were mainly located in the lowlands. The mapping of the deserted settlements and the GIS analysis of their spatial characteristics reveals a variety of desertion patterns. The causes of abandonment remain largely elusive. However, the examination of specific case studies shows that apart from the anticipated repercussions of war, other factors equally affecting the desertion patterns include environmental variables, as well as socioeconomic and related demographic changes.